(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This paper investigated contractor’s performance in Iraq. Determination and ranking the factors that affecting on the contractors’ performance in construction projects are done. A field survey of 45 Iraqi contractors work in construction contracting companies (general and private sector) was under taken using structured questionnaires. The most effective factors on the contractor’s performance were obtained using Relative Importance Index (RII). The work revealed that: cash flow of project, average delay in regular payments, contractor experience, design team experience, and site preparation time are the major factors influence on contractor’s performance in construction project.